Pembelajaran Partisipatif Melalui Posyandu Lansia: Penguatan Kapasitas Lansia Berbasis Active Ageing di Kampung Suryowijayan, Kelurahan Gedongkiwo - Safa Nuraini Yunisawijayanti; Firda Aulia Zahro; Dewi Cahyani Puspitasari (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
The increasing population of older adults in Indonesia presents new challenges in ensuring they are valued, socially connected, and capable of managing their health independently. This field lecture program aims to enhance the capacity of older adults by establishing the “Surya Melati” Older Adult Posyandu in Suryowijayan, Gedongkiwo, guided by the principles of active aging. Combining community-based learning, Participatory Action Research, and community engagement, the program creates a dialogic space for students, facilitators, and older adults to share and understand each other's daily experiences. Results indicate that, for older adults, feeling healthy depends not only on physical strength but also on light social interactions, group singing, simple finger exercises, and environmental care. The posyandu activities act as a gathering point for sharing stories and maintaining enthusiasm for daily life. Facilitators play a crucial role as companions and mobilizers, despite challenges such as fluctuating participant motivation, limited staff, and a lack of operational guidelines. Interactions between students and older adults foster new awareness of the importance of supportive, welcoming social environments in aging. Overall, the program shows that an older adult posyandu is more than a health service; it is a shared learning space that helps older adults stay active and engaged. These findings provide a foundation for future programs that are more inclusive and responsive to the needs of older adults with limited mobility or specific challenges.